2018
DOI: 10.5306/wjco.v9.i4.56
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and oral potentially malignant disorders: Critical appraisal and prospects

Abstract: Quality of life (QoL) is a vital and often required health outcome measure that is relevant to patient care. A healthy oral cavity enables person to perform daily activities without any limitations. However, any disturbance may result in impaired QoL. The oral health-remains an essential element of people’s health and well-being. In recent years, the tradition of clinical practice and research has been changed by incorporating QoL assessment, as it helps in assessment of patients’ needs and monitoring treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…It is also very important to take preventive measure like avoid going to dusty area or construction site, wear N95 mask, avoid activities that has direct contact with dust or soil, clean oxygen mask, humidifier. My patient show great improvement after getting the treatment and the treatment was still going on discharge [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also very important to take preventive measure like avoid going to dusty area or construction site, wear N95 mask, avoid activities that has direct contact with dust or soil, clean oxygen mask, humidifier. My patient show great improvement after getting the treatment and the treatment was still going on discharge [19].…”
Section: Discussionmentioning
confidence: 98%
“…Over the last few decades, the covid 19 has increased all over the world. More issues are likely to be observed as covid 19 The main cause of Oral Candidiasisi and Subcutaneaous Emphyema SARI is mostly bacterial or fungal infection, foreign bodies or any chemical agents. Due to these factors, organs or tissues may perforate and becomes infected.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article, Gondvikar SV et al analysed the effects of socioeconomic status (SES) and its variables on the QoL in patients diagnosed with OSMF. He reported that patients with lower SES were diagnosed with advanced stages of OSMF with poor QoL, thereby highlighting the importance of SES as a major determinant [22].…”
Section: Discussionmentioning
confidence: 99%
“…Few articles reflected on effective diagnostic tools and evaluation of abdominal malignancies [10][11] . Number of articles reflected on various aspects of different types of carcinoma prevalent in this region 12-24. Some articles on prevalent, potentially pre-malignant lesions and conditions were reviewed [25][26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%